The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/14651858.cd012730.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for induction and maintenance of remission in Crohn's disease

Abstract: Analysis 2.3. Comparison 2 Rifaximin (800 mg to 2400 mg daily) versus placebo, Outcome 3 Adverse events.. .. Analysis 2.4. Comparison 2 Rifaximin (800 mg to 2400 mg daily) versus placebo, Outcome 4 Serious adverse events. Analysis 2.5. Comparison 2 Rifaximin (800 mg to 2400 mg daily) versus placebo, Outcome 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In the 3rd European evidence-based consensus, the use of antibiotics in CD patients is appropriate for septic complications, symptoms attributable to bacterial overgrowth or perineal disease (133). However, a Cochrane database systematic review in 2019 reported that the efficacy of antibiotics in inducing remission of CD appeared be modest and might not be clinically meaningful (134). The effect on the maintenance of remission and the risk of severe adverse events in CD was unclear.…”
Section: Antibioticsmentioning
confidence: 99%
“…In the 3rd European evidence-based consensus, the use of antibiotics in CD patients is appropriate for septic complications, symptoms attributable to bacterial overgrowth or perineal disease (133). However, a Cochrane database systematic review in 2019 reported that the efficacy of antibiotics in inducing remission of CD appeared be modest and might not be clinically meaningful (134). The effect on the maintenance of remission and the risk of severe adverse events in CD was unclear.…”
Section: Antibioticsmentioning
confidence: 99%
“…Patients who had undergone ileal resection and were treated with metronidazole, an antibiotic that is usually ineffective in patients with ileitis (180), exhibited a delay in symptomatic recurrence (181). A systematic review of antibiotic therapy in CD patients found that antibiotics likely have a modest effect that may not be clinically relevant (182). Furthermore, to maintain antibiotic treatment efficacy and prevent relapse, longterm treatment is required, as with all therapies for CD (183,184).…”
Section: Therapeutic Targeting Of the Intestinal Microbiota Antibiotimentioning
confidence: 99%
“…Biofilms play a role in Crohn’s Disease pathology [29], and infection-associated biofilms are often sources of persistence, antibiotic resistance, and tolerance [74,75]. Antibiotic therapy is routinely used as an intervention in CD, and is known to temporarily ameliorate symptoms in the majority of patients [76]. However, relapse during treatment is common and reportedly universal [77] when treatment is halted, suggesting inflammation in relapsing CD may be due to outgrowth of antibiotic resistant or surviving, tolerant bacteria, such as those in mucosa-associated AIEC biofilms.…”
Section: Discussionmentioning
confidence: 99%